Gan-jiang-ling-zhu decoction improves steatohepatitis by regulating gut microbiota-mediated 12-tridecenoic acid inhibition - Xu, Ruohui; Wu, Jiaxuan; Pan, Jiashu; Zhang, Shengan; Yang, Yunuo; Zhang, Li; Zhou, Wenjun; Wu, Na; Hu, Dan; Ji, Guang; Dang, Yanqi (Frontiers in Pharmacology, 2024)
Introduction: Gan-jiang-ling-zhu (GJLZ) decoction is a classical traditional Chinese medicine prescription. Through invigorating yang, activating qi and dissipating dampness, GJLZ decoction is widely applied for the treatment of chronic digestive disease, including nonalcoholic fatty liver disease. However, efficacy and mechanism of GJLZ decoction behind nonalcoholic steatohepatitis (NASH) treatment remains unelucidated.Methods: NASH was induced in mice, followed by treatment with GJLZ decoction.Various methods including hematoxylin-eosin, oil red O staining, and triglyceride analysis were employed to evaluate the treatment effects of GJLZ decoction on NASH. Gut microbiota, metabolomics, cell viability assays, immunofluorescence and western blotting were performed to unveil the mechanism behind GJLZ decoction.: GJLZ decoction treatment significantly improved hepatic steatosis in mice with NASH. It led to remodeling of gut flora and metabolite structures, including the 12-tridecenoic acid level. 12-Tridecenoic acid aggravated hepatic steatosis by promoting acetyl-coenzyme A carboxylase alpha (ACC) expression and inhibiting carnitine palmitoyltransferase 1A (CPT1A) expression. GJLZ decoction treatment reduced the 12-tridecenoic acid level, inhibited ACC activity and promoted CPT1A expression. Conclusion: Our results demonstrated that 12-tridecenoic acid aggravated hepatic steatosis by affecting the ACC-CPT1A axis and GJLZ decoction treatment effectively reduced the 12-tridecenoic acid level and improved steatosis.